Low-sodium hollow salt capable of dietary supplement of astaxanthin and preparation method of low-sodium hollow salt
Through emulsion spray drying technology of Radix Rheumata protein-chitosan complex carrier, low-sodium hollow salts loaded with antioxidant properties and rich flavors were prepared, which solved the structural stability of the hollow salt and the single nutritional content of the hollow salt. The problem has improved the bioavailability of astaxanthin and the antioxidant properties of food.
Patent Information
- Application Number
- CN202411402107.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing spray-dried hollow salts have poor structural stability, single nutrients, poor antioxidant properties and poor taste. They also have poor water solubility and low bioavailability, making it difficult to be used as a nutritional supplement in the food industry. Widely used.
Using the Radix Radix Protein-Chitosan Complex as a carrier, low-sodium hollow salts loaded with astaxanthin were prepared by emulsion spray drying, improving the stability and bioavailability of astaxanthin and providing antioxidant in foods Performance and rich flavor.
Achieves a 30-50% sodium reduction effect without losing saltiness, improves the daily dietary supplement of astaxanthin, enhances the antioxidant properties and taste of food, and does not contain surfactants, ensuring long-term storage. astaxanthin retention and lipid oxidation stability.
Smart Images

Figure CN119257227A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hollow microspheres, and in particular relates to a low-sodium hollow salt loaded with astaxanthin and a preparation method thereof. Background Art
[0002] Sodium chloride (NaCl) is the main source of saltiness in food and is the most widely used condiment in the daily diet, contributing to the texture and preservation of food. According to the World Health Organization, the current global average daily sodium intake is 4.5-6 g / day, far exceeding the recommended 2.4 g / day. Excessive sodium intake in the diet is closely associated with high blood pressure and an increased risk of stroke and cardiovascular disease. Therefore, there is an urgent need to reduce the sodium content in processed foods.
[0003] Spray-dried salt microspheres with emulsion as carrier are considered as a new salt substitute. By controlling the structure and distribution of the microspheres, they can reduce sodium without losing taste. For example, Mint has developed hollow salt using amphiphilic biopolymers such as gum arabic, which can reduce sodium by 25-50% in applications such as bread and salty snacks. Hollow microspheres with smaller size and high specific surface area can increase the accessibility of NaCl to target receptors on taste bud cells, thereby enhancing salty taste perception. Yang Xiaoquan et al. used nanoemulsion droplets as carriers, prepared hollow salt by spray drying, and used the oil phase as the flavor source. However, existing spray-dried hollow salts still have problems such as poor structural stability, single nutritional ingredients, poor antioxidant properties, and poor taste.
[0004] Astaxanthin is a beneficial carotenoid known for its antioxidant properties and plays a vital role in human health. It is primarily used to combat oxidative stress and prevent various diseases such as cardiovascular disease, inflammation, and cancer. However, astaxanthin has poor water solubility, low bioavailability, and is easily degraded by oxygen, light, and high temperature. These limitations have hindered its widespread use as a nutritional supplement in the food industry. Summary of the invention
[0005]
Technical issues
[0006] Hollow salt can reduce sodium intake and is beneficial to human health. However, existing spray-dried hollow salts have the problems of single nutritional ingredients, poor antioxidant properties, and limited taste. Astaxanthin can be used to combat oxidative stress and prevent various diseases, but it has poor water solubility, low bioavailability, and is easily degraded by oxygen, light, and high temperature, making it difficult to use as a nutritional supplement in the food industry. There is a need for a hollow salt that can supplement astaxanthin with antioxidant properties and rich taste.
[0007]
Technical solution
[0008] In view of the above technical problems, the present invention utilizes emulsion as an effective delivery system for astaxanthin to improve the stability and bioavailability of astaxanthin; based on the Haematococcus pluvialis protein-chitosan complex, a low-sodium hollow salt loaded with astaxanthin with antioxidant properties and rich taste is prepared to provide a salt substitute for dietary astaxanthin supplementation.
[0009] The present invention provides a method for preparing a low-sodium hollow salt capable of supplementing astaxanthin in a dietary manner, comprising the following steps:
[0010] (1) Preparation of the complex: Dissolve the Haematococcus pluvialis protein and food-grade polysaccharide in water, adjust the pH and stir to obtain a complex solution;
[0011] (2) Preparation of salt Pickering emulsion: NaCl and oil are added to the complex solution, dispersed at high speed and subjected to high pressure homogenization to obtain an oil-in-water Pickering emulsion;
[0012] (3) Preparation of hollow salt: The water-in-oil Pickering emulsion is spray-dried to obtain a low-sodium hollow salt loaded with astaxanthin.
[0013] In one embodiment of the present invention, in step (1), the method for extracting Haematococcus pluvialis protein is: dissolving Haematococcus pluvialis and NaCl in water, performing ultrasonic treatment to obtain a dispersed system, extracting the Haematococcus pluvialis protein by ammonium sulfate precipitation method, and removing ammonium ions by dialysis.
[0014] In one embodiment of the present invention, in the method for extracting Haematococcus pluvialis protein, the concentration of Haematococcus pluvialis in the dispersed system after ultrasound is 4-6 wt %, and the concentration of NaCl is 1.5-3 wt %.
[0015] In one embodiment of the present invention, in the method for extracting Haematococcus pluvialis protein, the ammonium sulfate precipitation method is to add ammonium sulfate (0.662 g / mL) to the dispersed system to precipitate the protein in the supernatant, and after centrifugation at 12000 rpm at 4°C, collect the precipitate of Haematococcus pluvialis protein.
[0016] In one embodiment of the present invention, in the method for extracting Haematococcus pluvialis protein, the dialysis method is to dissolve the precipitate of Haematococcus pluvialis protein in deionized water and dialyze it at 4°C using a 3500Da dialysis bag for 48 hours.
[0017] In one embodiment of the present invention, in step (1), the food-grade polysaccharide is one or more of chitosan, gum arabic, carrageenan, maltodextrin, β-glucan, xanthan gum, and konjac mannose.
[0018] In one embodiment of the present invention, in step (1), the food-grade polysaccharide is chitosan, and 0.4% glacial acetic acid by weight of water is added when dissolving chitosan in water.
[0019] In one embodiment of the present invention, in step (1), the mass ratio of Haematococcus pluvialis protein to food-grade polysaccharide is 1:0.5 to 1:4.
[0020] In one embodiment of the present invention, in step (1), the mass ratio of Haematococcus pluvialis protein to food-grade polysaccharide is preferably 1:2.
[0021] In one embodiment of the present invention, in step (1), the total mass fraction of the Haematococcus pluvialis protein and the food-grade polysaccharide in the complex solution is 0.5-2%.
[0022] In one embodiment of the present invention, in step (1), the pH is adjusted to 3-7, the stirring temperature is 20-50° C., and the stirring time is 4-8 h.
[0023] In one embodiment of the present invention, in step (1), the pH is adjusted to 5, the stirring temperature is preferably 25° C., and the stirring time is preferably 6 h.
[0024] In one embodiment of the present invention, in step (2), the NaCl concentration of the complex solution is 20-30 g / 100 mL.
[0025] In one embodiment of the present invention, in step (2), the NaCl concentration of the complex solution is preferably 25 g / 100 mL.
[0026] In one embodiment of the present invention, in step (2), the oil is one or more of soybean oil, corn oil, and sunflower oil.
[0027] In one embodiment of the present invention, in step (2), the mass ratio of the complex solution to the oil is 85:15 to 95:5.
[0028] In one embodiment of the present invention, in step (2), the oil is soybean oil, and the mass ratio of the complex solution to the soybean oil is preferably 90:10.
[0029] In one embodiment of the present invention, in step (2), the rotation speed of high-speed dispersion is 10000-15000 rpm, and the dispersion time is 3-10 min.
[0030] In one embodiment of the present invention, in step (2), high-speed dispersion is performed in a high-speed disperser, and the model of the high-speed disperser is MICCRA D-4.
[0031] In one embodiment of the present invention, in step (2), the pressure of high-pressure homogenization is 200 to 1200 bar, and the cycle is 2 to 4 times.
[0032] In one embodiment of the present invention, in step (2), the high-pressure homogenization equipment is GEA.
[0033] In one embodiment of the present invention, in step (3), the spray drying conditions are as follows: the injection port temperature is 140-200°C, the output port temperature is 70-100°C, the injection rate is 4-16 mL / min, the vacuum fan rate is 70-100%, the air flow meter is 20-30 mm, and the vacuum degree is -50--100 mbar.
[0034] In one embodiment of the present invention, in step (3), the spray drying equipment is BUCHI B-290.
[0035] The present invention also provides a low-sodium hollow salt loaded with astaxanthin prepared according to the preparation method.
[0036] In one embodiment of the present invention, the low sodium hollow salt comprises: 40-80 wt% NaCl, 5-30 wt% mixture of protein and polysaccharide, 12-30 wt% edible oil, and 0.2-2 wt% water.
[0037] The present invention also provides application of the functional salt loaded with astaxanthin in the field of food.
[0038] In one embodiment of the present invention, the food includes dry sprinkle type and cold mixed type food.
[0039] Beneficial effects:
[0040] The low-sodium hollow salt for dietary supplementation of astaxanthin according to the present invention does not contain any surfactant.
[0041] The low-sodium hollow salt for dietary supplementation of astaxanthin of the present invention can achieve a sodium reduction effect of 30-50% without losing the salty taste.
[0042] The low-sodium hollow salt for dietary supplementation of astaxanthin of the present invention encapsulates astaxanthin in an oil phase to solve the problems of poor water solubility and low bioavailability, thereby increasing the daily dietary supplementation of astaxanthin.
[0043] The spray-dried product obtained by using the emulsion as a carrier has good astaxanthin retention rate and lipid oxidation stability under long-term storage.
[0044] The low-sodium hollow salt capable of supplementing astaxanthin in a dietary manner can effectively prevent the fat oxidation of fried steak, thus being beneficial to maintaining the food quality thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The particle size (A), particle size distribution (B), appearance (C) and cryo-SEM (D) test results of water-in-oil Perking emulsion.
[0046] Figure 2 The thermal image (A), relaxation time (B), MRI (C), and relative signal intensity of MRI (D) of oil-in-water Perking emulsion.
[0047] Figure 3 These are the rheological properties test results of water-in-oil Perking emulsion.
[0048] Figure 4 These are the test results of the morphology and particle size of low-sodium hollow salt loaded with astaxanthin.
[0049] Figure 5 These are the surface element determination results of low sodium hollow salt loaded with astaxanthin.
[0050] Figure 6 These are the results of the determination of astaxanthin stability and lipid oxidation stability of low sodium hollow salt loaded with astaxanthin.
[0051] Figure 7 is the NaCl and 2% HPP-CS hollow salt (Example 4) + Release characteristics, XRD and sensory test results.
[0052] Figure 8 This is a test of the oxidative stability of fried steaks with NaCl and 2% HPP-CS hollow salt (Example 4). DETAILED DESCRIPTION
[0053] The present invention is described in detail below with reference to embodiments, but the embodiments of the present invention are not limited thereto.
[0054] The raw materials used in the examples and comparative examples of the present invention are: NaCl purchased from Dalian Salt Chemical Group, Haematococcus pluvialis powder purchased from Kunming Baiou Biotechnology Co., Ltd., chitosan purchased from Shanghai Yuanye Biotechnology Co., Ltd., and soybean oil purchased from Jinlongyu. Test method of water-in-oil Pickering emulsion:
[0055] Particle size: The particle size of the emulsion samples was measured using a Zeta sizer Nano instrument (Malvern Instruments, UK). Prior to measurement, the emulsion samples were diluted to transparency and 1 mL of the sample was used for analysis.
[0056] SEM: The morphology of the emulsions was analyzed using a Hitachi SU8010 cryo-SEM. The emulsion was placed on a sample stage and quickly frozen with liquid nitrogen to preserve its initial state. The frozen droplet was then cut to expose the cross section and gold plated using a cryogenic preparation delivery system under vacuum. The sample was subsequently transferred to a -145°C SEM test chamber for examination.
[0057] Thermal properties: Differential scanning calorimetry (DSC) (DSC-250, TA, USA) was used to analyze the thermal properties of the samples. About 10 mg of the sample was placed in an aluminum pan, and an empty pan was used as a control. During the programmed heating process, high-purity nitrogen was used as the protective gas, and the sample was heated from -40°C to 40°C at a rate of 5°C / min.
[0058] Low-field NMR: Low-field NMR (LF-NMR) and magnetic resonance imaging (MRI) analysis was performed on the samples using a LF-NMR analyzer (Newmag Analytical Instruments Co., Ltd., Suzhou, China). The samples were inserted into the NMR probe and the signal was collected by the Carr-Purcell Meiboom-Gill (CPMG) sequence to measure the transverse relaxation time (T 2 ). Experimental parameters include P 1 (90° pulse), P 2 (180° pulse), TW (π value) and number of echoes were set to 32μs, 64μs, 1500ms and 10000, respectively. MRI was performed by spin echo sequence with specified acquisition parameters, slice width of 2.5mm, repetition time (T R ) is 1600ms, T 1 Weighted image echo time (T E ) was 50 ms. The permanent magnet was maintained at a temperature of 32° C. and a magnetic field strength of 0.5 T was used. The grayscale images of the MRI images were analyzed using OsiriX software (Pixmeo, Switzerland).
[0059] Rheological properties: The rheological properties of the salt Pickering emulsions were examined using a DHR-2 rheometer (TA Instrument, USA). Four scanning modes were used: (1) frequency sweep from 0.1 to 1 Hz at a constant strain of 0.5%; (2) strain sweep from 0.01% to 100% at 1 Hz and 25 °C; (3) frequency sweep from 0.1 to 100 s at 25 °C. -1 The apparent viscosity is measured at a shear rate of 1 Hz; (4) the temperature is increased from 10°C to 80°C at a frequency of 1 Hz and a strain of 0.1%.
[0060] Test method for loaded astaxanthin functional salt:
[0061] Sodium content determination: Freshly spray-dried salt powder (0.5 g) was added to a mixed acid solution consisting of perchloric acid and nitric acid in a ratio of 1:9, and then heated to digest until the solution became clear and white smoke emerged. The digested solution was then diluted to 25 mL with deionized water for Na + Content analysis. Cesium chloride solution (0.2% m / v) was introduced into the final assay solution and the corresponding blank solution. The Na in the diluted samples was measured using AA-240 flame atomic absorption spectrometry at 589 nm. + content.
[0062] SEM and EDS: The morphology of the hollow salts was characterized by SEM (JSM-7800F, Japan). Approximately 50 particles were analyzed directly from the SEM images using ImageJ software (version 1.52a, National Institutes of Health, USA), maintaining their original magnification, to determine the particle diameter and size distribution. The surface elemental composition (Na, Cl, O, C, and N) of the hollow salt particles was examined using a SEM instrument equipped with an energy dispersive X-ray spectroscopy (EDS) detector (X-Max50, UK).
[0063] XRD: The crystallinity and grain size of the salt particles were evaluated using an X-ray diffractometer (XRD-7000S, Japan). CuKα radiation (wavelength ) The samples were analyzed under the working conditions of 40 mA and 45 kV. The 2θ scanning range was from 10° to 70°, the step size was 0.003°, and the scanning speed was 50 s / step. In addition, the grain size of the samples was determined using the Debye-Scherrer equation (Equation 1);
[0064] D=Kλ / (βcosθ) (1)
[0065] Here, D represents the grain size of the sample, K represents the dimensionless shape factor, λ represents the wavelength of the CuKα radiation, β represents the full width at half maximum intensity, and θ is the Bragg angle.
[0066] Moisture content and water activity: The moisture content of freshly spray-dried hollow salt powder was assessed gravimetrically. A mass of W was added to the crucible. 0 Hollow salt powder, record the total mass W of the crucible and the hollow salt powder 1 , then dry at 105°C to constant weight, and record the total mass W of the crucible and the hollow salt powder 2 , and thus calculate the water content (%) = 100 × (W 1 -W 2 ) / W 0 The water activity (aw) was measured using a water activity meter (Aqua Lab 4TE, USA) with a sensitivity of ±0.001.
[0067] Chroma: The color value of the hollow salt was measured using a HunterLab spectrophotometer (ColorFlex EZ, USA). Before analysis, calibration was performed using black glass and white tiles. The results are presented based on L* (brightness), a* (red-green), and b* (blue-yellow) values (Lima et al., 2021). The color difference between the control sample and the changed sample was calculated using equation (2).
[0068]
[0069] Total oil content: The total oil content of the hollow salt was determined by hexane extraction gravimetric method. A sample weighing 0.5 g was dispersed in 15 mL of deionized water, 30 mL of hexane was introduced, and the mixture was shaken vigorously to ensure complete extraction of the oil. The mixture was then centrifuged at 4500 rpm for 5 minutes. The upper layer containing the extracted oil was collected and dried at 60 ° C until constant weight was reached, and the total oil content was weighed.
[0070] Surface oil content: 15 mL of hexane was added to 1.5 g of the hollow salt sample, and then stirred at 150 rpm for 2 minutes. The mixture was then filtered through filter paper, and the residue was washed three times with 20 mL of hexane. The filtrate was collected and dried at 60 ° C until constant weight was reached, and the surface oil content was weighed.
[0071] The packaging efficiency is determined by equation (3);
[0072] Packaging efficiency (%) = (TO-SO) / TO × 100 (3)
[0073] Where TO represents the total oil content and SO represents the surface oil content extracted per unit mass of spray-dried powder.
[0074] Astaxanthin storage stability: The storage stability of the hollow salt powder was studied by measuring the astaxanthin content of the hollow salt powder during storage at 50°C for 15 days using a UV-visible spectrophotometer (Lambda 35, USA). Initially, 0.2 g of the hollow salt containing astaxanthin was mixed with 4.8 mL of a mixed solvent (dichloromethane: methanol = 2:1 v / v). After stirring, the sample was centrifuged at 8000 rpm for 10 min, and then the absorbance of the organic phase was measured at 480 nm to determine the astaxanthin content.
[0075] LH measurement: Freshly spray-dried hollow salt powder was stored at 50 °C for 15 days to evaluate the oxidation of soybean oil. To detect the main lipid oxidation products, 0.2 g of hollow salt powder was mixed with 1.5 mL of mixed solvent (2-propanol: isooctane = 1:3 v / v) and stirred for 3 minutes. The suspension was then centrifuged (8000 rpm, 5 min), and then 2.8 mL of methanol / 1-butanol (2:1, v / v) was added to the supernatant, and 15 μL of ferrous sulfate and ammonium thiocyanate solutions were introduced, respectively. After 20 min of dark reaction, the absorbance at 510 nm was recorded. Using H 2 O 2 The LH content was determined using a standard curve.
[0076] MDA determination: 0.2g of hollow salt powder was mixed with a solution containing 4mL of thiobarbituric acid (TBA) and 1.8mL of deionized water. TBA solution, comprising 0.375g of TBA dissolved in 100mL of 0.25mol / L HCl, and 15g of trichloroacetic acid was added. The mixture was then heated at 95°C for 10min and subsequently cooled. After centrifuging the solution (8000rpm, 5min) to obtain the supernatant, the absorbance was measured at 532nm. The malondialdehyde (MDA) content was quantified using a standard curve prepared using 1,1,3,3-tetraethoxypropane.
[0077] Electronic tongue assay: The Astrie electronic tongue detection system (Alpha MOS, France) was used to identify the flavor intensity of the hollow salt. The powder sample was dissolved in the solution and incubated at 37 °C to simulate the oral temperature. The sensor was immersed in the sample and data was collected once per second. Principal component analysis (PCA) was performed using the built-in software.
[0078] Sensory panel assessment: 18 healthy assessors aged between 18 and 35 years without taste disorders were recruited. Before the main experiment, they performed a series of screening tests, including triangle test, ranking test and salinity threshold test. Finally, 14 qualified sensory assessors (male to female ratio 1:1) were selected to conduct all sensory evaluations in this work.
[0079] Beef was purchased from Qianhe Market in Dalian, cut into small pieces of uniform size and then fried at 180℃ for 3min. Pre-measured salt samples were sprinkled evenly on the cooked beef. Sensory evaluation was conducted in a controlled sensory panel room under double-blind conditions. Each piece of steak seasoned with salt was placed in a covered sensory bottle labeled with a randomly assigned three-digit number. Panelists were instructed to evaluate and score attributes such as salinity, appearance, unpleasant odor, particle dispersion, and mouth texture using a 0 to 10 rating scale.
[0080] Antioxidant application of astaxanthin hollow salt in fried steak: Fresh steak was fried at 180°C for 3min. Subsequently, equal amounts of NaCl and hollow salt samples were evenly sprinkled on the surface of the steak. Then it was stored overnight at 4°C and 25°C, respectively. Finally, the steak with the fried surface was cut into small pieces, and 0.2g of steak sample was collected as the test sample. According to the method for lipid oxidation determination in Section 2.11, the lipid hydroperoxide (LH) and malondialdehyde (MDA) contents of the overnight steak were measured.
[0081] Example 1
[0082] A method for preparing a low-sodium hollow salt for dietary supplementation of astaxanthin comprises the following steps:
[0083] (1) Extraction of Haematococcus pluvialis protein: 100 g of Haematococcus pluvialis powder was weighed and dissolved in 2000 mL of water with constant stirring. 40 g of NaCl was added and ultrasonicated for 2 h to obtain a dispersed system. 0.662 g / mL of ammonium sulfate was added to precipitate the protein in the supernatant. After centrifugation at 12000 rpm at 4°C, the precipitate of Haematococcus pluvialis protein was collected and dialyzed at 4°C using a 3500 Da dialysis bag for 48 h.
[0084] (2) Preparation of the complex: 2 wt% Haematococcus pluvialis protein solution and 2 wt% chitosan solution with a glacial acetic acid concentration of 0.04 wt% were prepared in advance, 10 mL of the 2 wt% Haematococcus pluvialis protein solution and 20 mL of the 2 wt% chitosan solution were taken, and the solution was supplemented to 120 mL so that the total mass fraction of the Haematococcus pluvialis protein and chitosan was 0.5%, the pH was adjusted to 5, and stirred at 25°C for 6 h to obtain a complex solution.
[0085] (3) Preparation of salt Pickering emulsion: 30 g NaCl and 12 g soybean oil were added to the complex solution, and the mixture was treated with a MICCRA D-4 high-speed disperser at 12,000 rpm for 3 min. The mixture was homogenized with a GEA high-pressure homogenizer at 600 bar for 3 cycles to prepare an oil-in-water Pickering emulsion.
[0086] (4) Preparation of hollow salt: The water-in-oil Pickering emulsion was connected to a spray drying injection pump for spray drying. The spray drying conditions were: injection port temperature 160°C, output port temperature 90°C, injection rate 8 ml / min, vacuum rate 90%, air flow meter 25 mm, vacuum degree -80 mbar, and the powder was collected and stored in a cool and dry place to obtain a low-sodium hollow salt loaded with astaxanthin.
[0087] Example 2
[0088] A method for preparing low-sodium hollow salt for dietary supplementation of astaxanthin:
[0089] The difference from Example 1 is that in step (2), 20 mL of 2 wt% Haematococcus pluvialis protein solution and 40 mL of 2 wt% chitosan solution are taken, and the solution is supplemented to 120 mL, so that the total mass fraction of Haematococcus pluvialis protein and chitosan is 1%.
[0090] Example 3
[0091] A method for preparing low-sodium hollow salt for dietary supplementation of astaxanthin:
[0092] The difference from Example 1 is that in step (2), 30 mL of 2 wt% Haematococcus pluvialis protein solution and 60 mL of 2 wt% chitosan solution are taken and the solution is supplemented to 120 mL so that the total mass fraction of Haematococcus pluvialis protein and chitosan is 1.5%.
[0093] Example 4
[0094] A method for preparing low-sodium hollow salt for dietary supplementation of astaxanthin:
[0095] The difference from Example 1 is that in step (2), 40 mL of 2 wt% Haematococcus pluvialis protein solution and 80 mL of 2 wt% chitosan solution are taken and the solution is supplemented to 120 mL so that the total mass fraction of Haematococcus pluvialis protein and chitosan is 2%.
[0096] Comparative Example 1
[0097] A method for preparing hollow salt:
[0098] The difference from Example 1 is that 60 mL of 2 wt % Haematococcus pluvialis protein solution is taken and the solution is supplemented to 120 mL so that the mass fraction of the Haematococcus pluvialis protein is 1%.
[0099] Comparative Example 2
[0100] A method for preparing hollow salt:
[0101] The difference from Example 1 is that 60 mL of 2 wt % chitosan solution is taken and the solution is supplemented to 120 mL so that the mass fraction of chitosan is 1%.
[0102] The performance of the brine-oil Pickering emulsions and the functional salts loaded with astaxanthin prepared in Examples 1-4 and Comparative Examples 1 and 2 was tested, and the test results are as follows:
[0103] 1. Characterization of Oil-in-Water Pickering Emulsion
[0104] Particle size and SEM analysis
[0105] The droplet size and particle distribution of the oil-in-water Pickering emulsions in Examples 1-4 and Comparative Examples 1 and 2 are as follows: Figure 1 As shown in AB. The droplet size of the water-in-oil Pickering emulsion stabilized by the Haematococcus pluvialis protein-chitosan (HPP-CS) complex ranges from 750±59.15nm to 1385±450.15nm, and decreases with the increase of the concentration of the HPP-CS complex. The smaller the droplet size, the higher the emulsion stability. The stable droplet sizes of Comparative Examples 1 and 2 are 1058.5±47.03nm and 2098±122nm, respectively. The reason is that the size reduction of the HPP-CS complex and HPP particles promotes the effective adsorption of the emulsified particles at the oil-water interface, resulting in a smaller droplet size.
[0106] Figure 1 C is the appearance of the HPP-CS composite in the stable water-in-oil Pickering emulsion in Examples 1-4 and Comparative Examples 1 and 2. All emulsions appear as flowing liquids, and the orange color of the emulsions deepens with the increase of HPP content. The water-oil volume ratio of the emulsion is 90%, and the solid content is 25.5-27%. Cryo-SEM image ( Figure 1 D) shows that the water-in-oil Pickering emulsion prepared at a higher HPP-CS complex concentration exhibits smaller droplets, more uniform distribution between droplets, reduced aggregation, and improved stability. The droplets of the emulsion of Comparative Example 1 show obvious fusion, indicating poor stability. The droplet size of the emulsion of Comparative Example 2 is significantly larger than the droplet size of the other groups.
[0107] Thermal properties and low-field NMR analysis
[0108] In DSC measurement ( Figure 2 A), the temperature gradually increased from -20 ° C, the heat flow signal initially decreased (exothermic), and then increased (endothermic). The negative value indicates that the water phase in the water-in-oil Pickering emulsion has undergone cold water crystallization between -20 and 0 ° C (exothermic), and then the crystallized ice melts as the temperature continues to rise (endothermic). As the concentration of the HPP-CS complex increases, the temperature corresponding to the negative peak continues to move toward -20 ° C. Compared with the other groups, the water-in-oil Pickering emulsion in Example 4 exhibits a lower crystallization temperature, which indicates that it has higher stability.
[0109] Relaxation time (T 2 ) is distributed as Figure 2 B. The detection signal is divided into three regions: 0.1-10, 10-100 and 100-1000 ms, corresponding to strongly bound water, weakly bound water and free water, respectively. The lateral T of the stable emulsions in Examples 1-4 and Comparative Examples 1 and 2 2In the relaxation spectrum, two characteristic peaks were observed in the range of 10.35-51.11 ms and 178.34-410.27 ms. As the concentration of HPP-CS increased, the peak in the range of 100-1000 ms shifted to the left, indicating that a larger proportion of free water became bound water through interaction with other components. This change in water state indicates that the stability of the water-in-oil Pickering emulsion has been improved. Figure 2 C shows an MRI image sequence of an emulsion, where a higher water content (hydrogen protons) corresponds to a stronger signal in the MRI image ( Figure 2 D). As the concentration of HPP-CS composite particles increases, the color distribution of the MRI image becomes more and more uniform. In the emulsions of Comparative Examples 1 and 2, the uneven color distribution indicates that the dispersion of the water and oil phases is uneven, which may lead to reduced stability.
[0110] Rheological behavior analysis
[0111] Rheological properties are critical to the stability and functionality of emulsions containing high NaCl concentrations, especially in applications involving spray-dried hollow salts. Figure 3 A), except for Example 4, the G' and G" values of all samples were kept below 60, and the observed difference was minimal. This may be because the weak micro-network structure formed by droplet condensation under high ionic strength enables the emulsion to maintain a high flow state, which meets the prerequisite of the spray drying feed liquid. The precursor liquid with too high viscosity is easy to block the spray drying equipment, thereby affecting the production and preparation of hollow salts. In the strain sweep test ( Figure 3 B), from 0.01% to 100% strain range, the G' value of all emulsions is higher than the G' value at a strain below 1%, indicating that it mainly has elastic behavior and strong structural stability in this strain range. The increase in oscillation stress reflects the structural stability and elastic properties of the emulsion. The improvement of the structural stability of the emulsion is conducive to the stabilization of the hollow structure of the hollow salt. With the increase of strain, except for Comparative Example 1, the stress response of all emulsions tends to be stable in the range of 10-100% ( Figure 3 C). This observation may be due to the increase in NaCl concentration, which increases the viscosity of the system. Increasing the viscosity of the feed solution helps to enhance the stability of the hollow salt structure and reduce the particle size within the range of satisfying good fluidity. Figure 3 As shown in Figure 4, all emulsions exhibited typical shear thinning behavior, in which the network structure gradually deformed with increasing shear rate. At a shear rate of 3-10 1 / s, the apparent viscosity of the water-in-oil Pickering emulsion in Example 4 was less than 10, while for the other samples, the apparent viscosity was less than 1, indicating that all samples had strong fluidity. The apparent viscosity of the emulsion was positively correlated with the concentration of HPP-CS composite particles.
[0112] In addition, the thermal stability of the emulsions was evaluated by dynamic temperature sweep tests. Figure 3 As shown in Figure E, the G' values of all emulsions remain relatively unchanged in the temperature range of 20–70 °C, indicating reasonable thermal stability. The feed salt emulsion precursor has high thermal stability, which can reduce the thermal demulsification of emulsion droplets during spray drying, thereby improving the uniformity of the hollow salt powder. Figure 3 F shows that all emulsions exhibit typical shear-thinning behavior with increasing temperature. Specifically, the emulsions stabilized by 0.5% HC and 1% HPP maintain a low viscosity that remains stable during heating. The temperature at which the emulsions reach the lowest viscosity gradually increases with increasing HPP-CS complex concentration. Higher temperatures may weaken the stabilizing effect of ions on the emulsion structure, thereby further reducing the viscosity. In general, the emulsions stabilized by the HPP-CS complex exhibit excellent viscoelasticity and thermal stability. Based on these findings, increasing the concentration of the HPP-CS complex can enhance the rheological properties of emulsions containing high concentrations of NaCl.
[0113] 2. Characterization of the structure of low sodium hollow salt loaded with astaxanthin
[0114] SEM and EDS
[0115] Astaxanthin-loaded low-sodium hollow salt particles were prepared by spray drying a salt Pickering emulsion stabilized by HPP-CS complex. Figure 4 A shows the appearance of low sodium hollow salt. Figure 4 B~D show the microscopic morphology and average particle size of the low sodium hollow salt. Compared with Examples 1-2 and Comparative Examples 1-2, the low sodium hollow salt particles of Example 4 exhibit more uniform and smaller particle sizes and have a smooth surface. This shows that the content and size of the wall material are crucial to the stability of the surface structure of the low sodium hollow salt particles. Studies have shown that insufficient emulsification properties or low wall material content can cause cracks on the surface of low sodium hollow salt. Typically, NaCl particles are larger than 300 μm, while the smaller size and larger surface area of low sodium hollow salt particles contribute to the perception of saltiness because they dissolve faster during consumption. Figure 5 The EDS results showed that the surface of low-sodium hollow salt microspheres was mainly composed of Na and Cl. The low-sodium hollow salt with higher HPP-CS concentration showed lower Na content.
[0116] Physical properties
[0117] Moisture content and water activity are key parameters that determine the shelf life of a product. Generally, the moisture content of commercially available salt is between 0.91% and 7.36%. Too high a moisture content can easily lead to product deterioration. As shown in Table 1, the moisture content of low-sodium hollow salts in Examples 1 to 4 is 0.33 to 1.18%. The moisture content of low-sodium hollow salt particles increases with the increase in HPP content, which may be due to the hydrophilicity of HPP. Increasing temperature and accelerating evaporation rate during spray drying will reduce water activity (a w ). Higher aw levels are associated with decreased mobility because they increase the interaction of low-sodium hollow salt particles. w When the value is lower than 0.91, the growth of most bacteria can be inhibited. The aw of the low sodium hollow salt in Examples 1 to 4 is 0.09 to 0.11.
[0118] Table 1 Physical properties of hollow salt
[0119]
[0120]
[0121] Different letters in the same column indicate significant differences (p<0.05).
[0122] Color is an important factor affecting consumer acceptance of food products, and the chromaticity of low-sodium hollow salts is shown in Table 2. There were statistically significant changes in L*, a*, and b* values between samples (P<0.05), indicating that the concentration of HPP-CS complexes affects color parameters. HPP salts showed higher ΔE values and lower L* values, which were closely related to the presence of the natural pigment astaxanthin in the wall material (equivalent to 2% of the wall material).
[0123] Table 2 Chroma of hollow salt
[0124] L* a* b* ΔE Example 1 <![CDATA[36.39±0.01 b ]]> <![CDATA[12.83±0.02 e ]]> <![CDATA[38.68±0.03 a ]]> <![CDATA[40.96±0.23 b ]]> Example 2 <![CDATA[32.07±0.25 c ]]> <![CDATA[15.88±0.30 d ]]> <![CDATA[30.86±0.09 b ]]> <![CDATA[38.19±0.30 c ]]> Example 3 <![CDATA[29.63±0.54 d ]]> <![CDATA[17.32±0.38 c ]]> <![CDATA[27.54±0.05 c ]]> <![CDATA[38.13±0.56 c ]]> Example 4 <![CDATA[27.00±0.34 e ]]> <![CDATA[20.58±0.52 b ]]> <![CDATA[22.11±0.04 e ]]> <![CDATA[38.56±0.25 c ]]> Comparative Example 1 <![CDATA[22.54±0.19 f ]]> <![CDATA[24.06±0.29 a ]]> <![CDATA[25.64±1.32 d ]]> <![CDATA[45.22±0.47 a ]]> Comparative Example 2 <![CDATA[54.68±0.39 a ]]> <![CDATA[0.68±0.03 f ]]> <![CDATA[4.10±0.06 f ]]> -
[0125] Different letters in the same column indicate significant differences (p<0.05).
[0126] It can be clearly seen from Table 3 that there is no significant difference in the total oil content (16-20%) of the low sodium hollow salts of Examples 1-4 and Comparative Examples 1-2, indicating that an inlet temperature of 160°C is more suitable for drying HPP-CS hollow salts. Compared with Comparative Examples 1-2, the low sodium hollow salts prepared from the HPP-CS complex exhibit a lower surface oil content, which decreases with the increase in the concentration of the HPP-CS complex. In addition, the oil encapsulation efficiency also follows a similar trend. For hollow salt powders, lower surface oil content and higher encapsulation efficiency are beneficial to reducing the degradation of astaxanthin and lipid oxidation. This may be attributed to the electrostatic interaction between HPP and CS, which forms a thicker and tighter barrier around the oil droplets.
[0127] Table 3 Total oil, surface oil and encapsulation efficiency of hollow salt
[0128]
[0129]
[0130] Different letters in the same column indicate significant differences (p<0.05).
[0131] Astaxanthin and oxidative stability
[0132] The long-term stability of low-sodium hollow salt loaded with astaxanthin was investigated. Figure 6 A shows the astaxanthin retention rate of the low sodium hollow salts of Examples 1-4 and Comparative Examples 1-2 within 15 days at 50°C. After 15 days of storage, the astaxanthin retention rates of all low sodium hollow salts showed a downward trend. Specifically, in the low sodium hollow salts of Examples 1-4, the retention rates of astaxanthin were 41.39±2.88%, 47.42±0.75%, 56.24±1.32%, and 61.28±0.75%, respectively, and that of Comparative Example 1 was 36.02±1.07%. The residual astaxanthin levels in Examples 1-4 were higher than those in Comparative Example 1. This indicates that as the concentration of the complex increases, the protective effect of low sodium hollow salts on astaxanthin increases. At the same time, Figure 6 B gives a semi-logarithmic graph describing the retention rate of astaxanthin. The results show that the degradation behavior of astaxanthin can be effectively described by a first-order kinetic model. At 50°C, the half-lives of encapsulated astaxanthin in the low-sodium hollow salt of Examples 1-4 were 12, 14, 18 and 21 days, respectively, which are higher than the half-life of astaxanthin in the comparative example (Table 4). This shows that the incorporation of the HPP-CS complex significantly enhances the stability of astaxanthin, and the adsorption of the HPP-CS complex on the shell structure of the low-sodium hollow salt particles may affect the interaction between effective oxygen and astaxanthin. In addition, the crude extract of HPP has the ability to scavenge free radicals, thereby delaying the degradation of astaxanthin.
[0133] Table 4 Effect of HPP-CS complex on storage stability of astaxanthin in hollow salt
[0134]
[0135] The levels of lipid hydroperoxide (LH) and malondialdehyde (MDA) were measured in all samples to evaluate the antioxidant efficacy of the functional salts against lipid oxidation. Figure 6As shown in Figure 3, all samples showed similar LH levels, which then increased rapidly from the third day of storage. After 15 days, the LH levels in the low sodium hollow salts of Examples 2-4 were 43.77, 30.59, and 19.05 mmol / kg oil, respectively. The LH levels of Example 1 and Comparative Examples 1-2 were 2.82, 3.14, and 3.46 times that of Example 4, respectively. These findings suggest that the HPP-CS complex effectively inhibits oil oxidation within the particles. MDA levels were also evaluated ( Figure 6 D). After 15 days of storage, the MDA content was determined to be similar to that of LH. Compared with Comparative Example 2, the oxidation rate of the functional salt prepared with the HPP-CS complex was slower, indicating that the presence of astaxanthin inhibited the formation of oxidants. In addition, during the spray drying process, the HPP-CS complex formed a more impermeable shell that hindered the contact between the oil phase and the oxidant. The antioxidant activity of the HPP-CS complex in the low-sodium hollow salt can neutralize the free radicals around the oil droplets and protect the soybean oil from oxidation. In short, the low-sodium hollow salt stabilized with the HPP-CS complex can improve the stability of astaxanthin and soybean oil.
[0136] Na + Release and XRD determination
[0137] The Na content of low sodium hollow salt was evaluated + Release properties, such as Figure 7 A. Specifically, compared with NaCl, the Na + The release rate is significantly higher. Low sodium hollow salt releases 80% of Na in 10 seconds + Faster release of Na from low sodium hollow salt + This may lead to a stronger salty taste perception. Therefore, compared with standard table salt with the same sodium content, low-sodium hollow salt can be perceived as having a stronger salty taste. The perception of saltiness by taste receptors is related to the sodium content of food. + The release rate of Na + When they come into contact with salty taste receptors, they trigger a neural response that our brains interpret as a salty taste. + The release rate of Na in hollow salt affects how quickly these receptors are activated, thus affecting our perception of saltiness. + The rapid release may activate these taste receptors more quickly, resulting in a stronger salty taste ( Figure 7 B).
[0138] X-ray diffraction (XRD) analysis revealed the crystallinity and cubic lattice structure of the salt particles ( Figure 7C). The XRD spectrum shows a significant peak near 2θ=31.60°, which is characteristic of their cubic structure. NaCl shows clear and strong peaks, indicating its crystalline structure. In contrast, the XRD spectrum of the low-sodium hollow salt shows a decrease in the intensity of the Bragg peak, indicating a decrease in crystallinity. In addition, the XRD spectrum of the low-sodium hollow salt shows a slightly distorted cubic phase in the split reflection at the strong peak. In addition, the crystallite sizes of NaCl and low-sodium hollow salt were calculated to be 130.2nm and 46.7nm, respectively. These findings indicate that the atomization process significantly reduces the crystal size of the low-sodium hollow salt particles, favoring Na + Quick release.
[0139] Sensory analysis
[0140] Figure 7 D is the taste score output by the electronic tongue of NaCl and low-sodium hollow salt. The results show that the saltiness, astringency, bitterness, umami, richness and sourness of low-sodium hollow salt are significantly higher than those of NaCl. In addition, Figure 7 The PCA results in E further showed that there was a significant difference in the overall taste of low-sodium hollow salt and NaCl, with sample differences having a cumulative variance of 99.7% (PC1: 96.0%, PC2: 3.7%). The sensory evaluation results showed that there was no significant difference in the saltiness score of the steak, and no adverse effects were observed ( Figure 7 F). Studies have reported that the salinity of chitosan / acid / NaCl particles prepared at room temperature is 19.2-54.4% lower than that of NaCl with the same salinity. The enhanced salinity of low-sodium hollow salts may be attributed to the smaller NaCl crystals on the surface. + Widely distributed on the surface of low-sodium hollow salt microspheres, it leads to a larger specific surface area and faster dissolution, thus enhancing the perceived saltiness.
[0141] Oxidative stability of fried steak after salting
[0142] Sprinkle equal amounts of NaCl and low-sodium hollow salt powder ( Figure 8 A), and then placed at 4°C and 25°C overnight to determine the LH and MDA contents, respectively. Figure 8 B and 8C. It can be seen that there are significant differences in the LH and MDA contents of fried steaks stored at 4°C and 25°C, indicating that there is a continuous oxidation reaction in fried foods after overnight. Compared with the NaCl sample, the LH and MDA contents of fried steaks added with low-sodium hollow salt were significantly reduced at 4°C and 25°C. HPP-CS-based low-sodium hollow salt containing astaxanthin may be a potential salt product for fried foods, which can reduce the degree of oxidation before entering the mouth.
[0143] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a low-sodium hollow salt for dietary supplementation of astaxanthin, characterized in that: The following steps are involved: (1) Preparation of the complex: Dissolve the Haematococcus pluvialis protein and food-grade polysaccharide in water, adjust the pH and stir to obtain a complex solution; (2) Preparation of salt Pickering emulsion: NaCl and oil are added to the complex solution, dispersed at high speed and subjected to high pressure homogenization to obtain an oil-in-water Pickering emulsion; (3) Preparation of hollow salt: The water-in-oil Pickering emulsion is spray-dried to obtain a low-sodium hollow salt loaded with astaxanthin.
2. The preparation method according to claim 1, characterized in that: In step (1), the food-grade polysaccharide is one or more of chitosan, gum arabic, carrageenan, maltodextrin, β-glucan, xanthan gum, and konjac mannose.
3. The preparation method according to claim 1, characterized in that: In step (1), the method for extracting Haematococcus pluvialis protein is as follows: dissolving Haematococcus pluvialis and NaCl in water, performing ultrasonic treatment to obtain a dispersed system, extracting Haematococcus pluvialis protein by ammonium sulfate precipitation method, and removing ammonium ions by dialysis; the Haematococcus pluvialis concentration in the dispersed system is 4-6wt%, and the NaCl concentration is 1.5-3wt%.
4. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of Haematococcus pluvialis protein to food-grade polysaccharide is 1:0.5-1:4, and the total mass fraction of Haematococcus pluvialis protein and food-grade polysaccharide in the complex solution is 0.5-2%; the pH is adjusted to 3-7, the stirring temperature is 20-50° C., and the stirring time is 4-8 hours.
5. The preparation method according to claim 1, characterized in that: In step (2), the NaCl concentration of the complex solution is 20-30 g / 100 mL.
6. The preparation method according to claim 1, characterized in that: In step (2), the oil is one or more of soybean oil, corn oil and sunflower oil; and the mass ratio of the complex solution to the oil is 85:15 to 95:
5.
7. The preparation method according to claim 1, characterized in that: In step (2), the rotation speed of high-speed dispersion is 10000-15000 rpm, and the dispersion time is 3-10 min; the pressure of high-pressure homogenization is 200-1200 bar, and the cycle is 2-4 times.
8. The preparation method according to claim 1, characterized in that: In step (3), the spray drying conditions are: injection port temperature 140-200°C, output port temperature 70-100°C, injection rate 4-16 ml / min, vacuum fan rate 70-100%, air flow meter 20-30 mm, vacuum degree -50--100 mbar.
9. The low-sodium hollow salt loaded with astaxanthin prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the low sodium hollow salt according to claim 9 in the food field.
Citation Information
Patent Citations
Astaxanthin algae oil high internal phase emulsion and preparation method thereof
CN112655952A
Preparation method and application of high-water-dispersion H-type or J-type aggregate astaxanthin / whey protein / chitosan nanocomposite
CN113368006A
Microcapsule preparation rich in astaxanthin as well as preparation method and application of microcapsule preparation
CN113521027A
Preparation method of emulsion with protection and controlled release effects of astaxanthin
CN113662183A
Formula and preparation method of astaxanthin-loaded Pickering emulsion
CN116849355A
Cited By
Low-sodium salt containing phycocyanin and preparation method thereof
CN121014837A
A low sodium salt containing phycocyanin and a method for preparing the same
CN121014837B